Human Rhinovirus Infection Induces Airway Epithelial Cell Production of Human β-Defensin 2 Both In Vitro and In Vivo - Proud, David; Sanders, Scherer P; Wiehler, Shahina (The Journal of immunology (1950), 2004)
We hypothesized that airway epithelial cells, the primary site of human rhinovirus (HRV) infection, provide a link between the innate and specific immune response to HRV via production of human β-defensin (HBD)-2, a potent in vitro attractant and activator of immature dendritic cells. Infection of primary cultures of human epithelial cells with several HRV serotypes induced expression of HBD-2 mRNA and protein, indicating that HBD-2 production was independent of viral receptor usage or mechanisms of viral RNA internalization. Induction of HBD-2 was dependent upon viral replication and could be mimicked by transfection of cells with synthetic dsRNA, but was not dependent upon epithelial production of IL-1. Studies with stable epithelial cell lines expressing HBD-2 promoter constructs, as well as inhibitor studies in primary cells, both demonstrated that induction of HBD-2 involves activation of the transcription factor, NF-κB. Other transcription factors must also be activated by HRV infection, however, as expression of HBD-3 mRNA was also induced and there is no putative NF-κB recognition sequence in the promoter of this gene. HBD-2 showed no direct antiviral activity against HRV. In vivo infection of normal human subjects with HRV-16 induced expression of mRNA for HBD-2 in nasal epithelial scrapings. Increases in mRNA correlated with viral titer and with increased levels of HBD-2 protein in nasal lavages. This represents the first demonstration that HRV infection induces epithelial expression of HBD-2 both in vitro and in vivo, and supports the concept that HBD-2 may play a role in host defense to HRV infection.